PENYUSUNAN RENCANA PENGEMBANGAN SEKOLAH DI SDN KECAMATAN PADANG TIMUR KOTA PADANG - TUTI BERLINA PANJAITAN (Universitas Negeri Padang, 2016)
The goal of this research are to see information about the headmaster perception about preparation of school development plans. The population is 33 headmaster and the sample is all of the population. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are the headmaster perception about preparation of school development plans of elementary School Subdistrict East Padang of Padang City.